PERUBAHAN SOSIAL EKONOMI MASYARAKAT SEBALUM DAN SESUDAH PEMINDAHAN PUSAT PEMERINTAHAN DI KELURAHAN AIR PACAH KEMATAN KOTO TANGAH KOTA PADANG - Novi, Meki Mustia (Pendidikan Geografi, 2014)
This study aims to determine the socio-economic changes in society before and aftertransfer of the seat of government in the Village Water District of Pacah Tangah Koto Padangwhich include: 1) affordability of care, 2) the level of income and 3) livelihood.This research is descriptive. The population in this study were all families in the villageWater Pacah totaling 2,232 households. Samples were taken in 2 ways, the sample region takenwith porposive sampling technique (designation) is just RW III, RW IV, VI and RW RW X, due tothe 4 basic appointment the region which is a region that is closest to the center of the newgovernment, while the sample taken with proportional random sampling technique with aproportion of 10% that the sample amounted to 76 families.The results of the study found that: 1) There was a change in socioeconomic conditions,affordability aspect more smoothly, more fairly and more suitable in the management of ID card,birth certificate, family card, business license and health services, 2) There was a change in theincome of the population, before the removal of the central government where the average incomeof Rp 2.116 million - Rp 2.881 million / month, and 3) a change in livelihoods. Before the removalof the principal livelihood general laborers, working in the market and no livelihood, after theremoval of the many residents who have side jobs, such as services and merchants